Comparative floral and pollen morphology of some invasive and native impatiens species - Vinogradova, Yulia Konstantinovna; Kuklina, Alla Georgievna; Tkacheva, Ekaterina Vasilyevna; Ryabchenko, Andrey Sergeevich; Khomutovskiy, Maksim Igorevich; Shelepova, Olga Vladimirovna (Revista de la Universidad del Zulia, 2020)
To evaluate the hypothesis of competitive superiority of invasive species, we compared the invasive Impatiens parviflora DC. and I. Glandulifera royle, the naturalized I. Nevskii pobed. and the native I. Noli-tangere L. in the flowers’ morphometric characters at different phases of anthesis. The characters in which alien species have a competitive superiority over closely related I. Noli-tangere are revealed. Morphological variability was studied by morphometric observations of the following characters: bud: length and diameter; spurred sepal: length and width; spur: length and diameter; lateral sepal: length and width; largest petal: length and death; large lobe of lateral petal: length and width; small lobe of lateral petal: length and width; anther: length; stamen’s filament: length; calyptra: length and width; ovary: length and diameter; length of a style, length of a stigma. There is a tendency for alien Impatiens species of the earlier development of androecium and gynoecium: сaliptra is formed at the stage of uncolored bud, the pistil is differentiated in ovary, short style and stigma is formed at the stage of colored bud. No other flowers’ morphometric characters, representing competitive advantage of the invasive I. Glandulifera and I. Parviflora over the native I. Noli-tangere and naturalized I. Nevskii were identified.